2021
DOI: 10.1111/jocd.14525
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling for Hair Loss

Abstract: Background: Microneedling is a relatively novel therapeutic modality introduced in the 1990s where small, fine needles are used to create micro punctures in the skin. It is a minimally invasive procedure used for various dermatological conditions, including androgenetic alopecia (AGA). Objective and Methods:We comprehensively summarize the literature regarding microneedling in dermatology. We performed linear multivariable regressions to synthesize evidence from the clinical trials that investigated the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…MN therapy is seen as one advancement of the traditional treatment modality for AGA patients. There are already several evidences showed that MN therapy is effective in AGA to a certain degree, such as the results of a 12‐week randomized, comparative, evaluator‐blinded study on 94 male AGA patients reported by Dhurat et al 14 These results were also confirmed by other researchers, suggesting the effectiveness of MN therapy combined with other established AGA treatments, especially with topical minoxidil 9,11,15–17 . In the present study, our results demonstrated an improvement on cosmetic coverage over the scalp with minimal side effects after MN alongside with minoxidil in AGA patients, which was confirmed by the IGAS based on global photographs, PGAS and patient's final satisfaction.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…MN therapy is seen as one advancement of the traditional treatment modality for AGA patients. There are already several evidences showed that MN therapy is effective in AGA to a certain degree, such as the results of a 12‐week randomized, comparative, evaluator‐blinded study on 94 male AGA patients reported by Dhurat et al 14 These results were also confirmed by other researchers, suggesting the effectiveness of MN therapy combined with other established AGA treatments, especially with topical minoxidil 9,11,15–17 . In the present study, our results demonstrated an improvement on cosmetic coverage over the scalp with minimal side effects after MN alongside with minoxidil in AGA patients, which was confirmed by the IGAS based on global photographs, PGAS and patient's final satisfaction.…”
Section: Discussionsupporting
confidence: 87%
“…effectiveness of MN therapy combined with other established AGA treatments, especially with topical minoxidil. 9,11,[15][16][17] In the present study, our results demonstrated an improvement on cosmetic coverage over the scalp with minimal side effects after MN alongside with minoxidil in AGA patients, which was confirmed by the IGAS based on global photographs, PGAS and patient's final satisfaction. However, controversy about the optimal parameters still remains in MN plus minoxidil for AGA, including the types of microneedle devices, needle length, the intervals between the sessions and the number of sessions.…”
Section: F I G U R E 1 Flow Diagram the Chart Shows Patients Inclusio...supporting
confidence: 72%
“…Several theories have been proposed regarding the mechanism of action of microneedling, namely, the induction of Wnt proteins that regulate DP (dermal papilla) signaling to HFSCs (hair follicle stem cells), increased blood ow to the hair follicles, increased scalp metabolism of minoxidil, and increased absorption of topical treatments [23]. While many clinical trials have studied the effectiveness of microneedling in treating AGA, they are often small, nonrandomized, and have varying methodologies, making it di cult to compare results.…”
Section: 3: Microneedling E Cacymentioning
confidence: 99%
“…Minoxidil, finasteride, and low-level laser light therapy (LLLT) are FDA-approved therapy options for AGA, with a significant effect [45][46][47][48][49][50][51][52]. In addition, dutasteride [41,53], platelet-rich plasma (PRP) [54][55][56], photobiomodulation [50], and microneedling [57] are further treatment options for AGA. However, these treatment options are costintensive and also require lifelong treatment, thus may have side effects.…”
Section: Tcm Understanding Of Hair Lossmentioning
confidence: 99%